A critical review of AlGaN/GaN-heterostructure based Schottky diode/HEMT hydrogen (H2) sensors for aerospace and industrial applications. (December 2021) - Ajayan, J.; Nirmal, D.; Ramesh, R.; Bhattacharya, Sandip; Tayal, Shubham; Leo Joseph, L.M.I.; Raju Thoutam, Laxman; Ajitha, D.
Abstract: Hydrogen (H2 ) has been widely used in H2 fuelled vehicles, semiconductor fabrication, medical treatments, chemical industry and industrial aerospace applications. However, H2 is a highly explosive gas (if H2 concentration exceeds 4.65 vol% in air) and therefore, the risk is very high when it is used in applications. This increases the demand for the development of high performance H2 sensors. The unique properties of AlGaN and GaN such as wide band gap, outstanding physical, chemical and thermal stability, optical transparency, environmental friendliness, low sensing response time, non-toxicity and surface sensitivity makes them one of the most promising material systems for the development of H2 sensors. An ultra high sensitivity of 1.24 × 10 7 and an ultra low response time of 7 s and recovery time of 6 s have been reported for AlGaN/GaN Schottky Diode (SD) H2 sensors. On the other hand, an outstanding sensitivity of 1.6 × 10 7 and an extremely low response time of 2.5 to 3 s have been reported for AlGaN/GaN HEMT (High Electron Mobility Transistor) H2 sensors. Moreover, AlGaN/GaN heterostructure-based H2 sensors can be operated over 800 °C temperature. This article critically reviews the structures, fabrication and factors influencing the sensing performance of AlGaN/GaN SD/HEMT H2 sensors for future aerospace and industrial applications.